2016
DOI: 10.1158/1535-7163.mct-15-0963
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Driven Mechanism of Vemurafenib Resistance in Melanoma

Abstract: Melanoma is molecularly and structurally heterogeneous, with some tumor cells existing under hypoxic conditions. Our cell growth assays showed that under controlled hypoxic conditions, BRAF(V600E) melanoma cells rapidly became resistant to vemurafenib. By employing both a three-dimensional (3D) spheroid model and a two-dimensional (2D) hypoxic culture system to model hypoxia in vivo, we identified upregulation of HGF/MET signaling as a major mechanism associated with vemurafenib resistance as compared to 2D st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 48 publications
2
37
0
4
Order By: Relevance
“…upregulation. In addition, Qin et al (2016) also observed that melanoma spheroids composed of A375 cells presented a higher HIF-1α and VEGF expression than the same cells cultured in 2D and demonstrated that this metabolic variation can impact on cells sensitivity to vemurafenib.…”
Section: Lack Of Oxygenmentioning
confidence: 81%
See 3 more Smart Citations
“…upregulation. In addition, Qin et al (2016) also observed that melanoma spheroids composed of A375 cells presented a higher HIF-1α and VEGF expression than the same cells cultured in 2D and demonstrated that this metabolic variation can impact on cells sensitivity to vemurafenib.…”
Section: Lack Of Oxygenmentioning
confidence: 81%
“…highly expressed in hypoxic regions of the spheroids(Gong et al, 2015;Qin et al, 2016) Terashima et al (2016). In addition,Qin et al (2016) also observed that melanoma spheroids composed of A375 cells presented a higher HIF-1α and VEGF expression than the same cells cultured in 2D and demonstrated that this metabolic variation can impact on cells sensitivity to vemurafenib.In literature, it was also reported that HIF-1 regulates the expression of several antiapoptotic factors (e.g., Bak, Bax, Bcl-xL, Bcl-2, Bid, Mcl-1, NF-κB, p53, and survivin;Masoud & Li, 2015;Rohwer & Cramer, 2011). In addition,Qin et al (2016) also observed that melanoma spheroids composed of A375 cells presented a higher HIF-1α and VEGF expression than the same cells cultured in 2D and demonstrated that this metabolic variation can impact on cells sensitivity to vemurafenib.In literature, it was also reported that HIF-1 regulates the expression of several antiapoptotic factors (e.g., Bak, Bax, Bcl-xL, Bcl-2, Bid, Mcl-1, NF-κB, p53, and survivin;Masoud & Li, 2015;Rohwer & Cramer, 2011).…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…The expression of the ROR2 receptor induces a 10‐fold decrease in sensitivity to BRAF inhibition, with this population being induced via the upregulation of WNT5a, which stabilizes HIF‐1α levels during hypoxic conditions via increased SIAH2 expression (O'Connell et al, ). Recent studies using 3D melanoma spheroid models have also found that hypoxia‐driven upregulation of HGF/MET plays an important role in vemurafenib resistance and is prevalent in drug‐resistant melanoma patients and xenograft models (Qin et al, ). Together, the various studies strongly suggest that resistance to targeted therapy in melanoma can be driven by hypoxia.…”
Section: The Stromal Microenvironment In Resistance To Mapk Blockadementioning
confidence: 99%